Securing sustainable funding for viral hepatitis elimination plans. (5th December 2019) - Hatzakis, Angelos; Lazarus, Jeffrey V.; Cholongitas, Evangelos; Baptista‐Leite, Ricardo; Boucher, Charles; Busoi, Cristian‐Silviu; Deuffic‐Burban, Sylvie; Chhatwal, Jagpreet; Esmat, Gamal; Hutchinson, Sharon; Malliori, Minerva‐Melpomeni; Maticic, Mojca; et al.
Abstract: The majority of people infected with chronic hepatitis C virus (HCV) in the European Union (EU) remain undiagnosed and untreated. During recent years, immigration to EU has further increased HCV prevalence. It has been estimated that, out of the 4.2 million adults affected by HCV infection in the 31 EU/ European Economic Area (EEA) countries, as many as 580 000 are migrants. Additionally, HCV is highly prevalent and under addressed in Eastern Europe. In 2013, the introduction of highly effective treatments for HCV with direct‐acting antivirals created an unprecedented opportunity to cure almost all patients, reduce HCV transmission and eliminate the disease. However, in many settings, HCV elimination poses a serious challenge for countries' health spending. On 6 June 2018, the Hepatitis B and C Public Policy Association held the 2nd EU HCV Policy summit. It was emphasized that key stakeholders should work collaboratively since only a few countries in the EU are on track to achieve HCV elimination by 2030. In particular, more effort is needed for universal screening. The micro‐elimination approach in specific populations is less complex and less costly than country‐wide elimination programmes and is an important first step in many settings. Preliminary data suggest that implementation of the World Health Organization (WHO) Global Health Sector Strategy on Viral Hepatitis can be cost saving. However, innovative financing mechanisms are needed to raise funds upfront for scaling up screening, treatment and harm reduction interventions that can lead to HCV elimination by 2030, the stated goal of the WHO.